Optimalisasi Tempat Pembuangan Sampah Untuk Meningkatkan Kesadaran Kebersihan Di Lingkungan Balai Desa Tanjung Serayan Kecamatan Mesuji Kabupaten Mesuji - Aryanika, Septa; Rifda Fahira; Nova Aini; Sri Wulandari; Ade Rizki Ronaldo; Rani Ristia Lanvi; Alya; Muhamad Adnan Nashrullah; Ferdi Jumansyah Putra (Wisanggeni: Jurnal Pengabdian Masyarakat, 2024)
Waste management is a significant challenge in Tanjung Serayan Village, Mesuji Regency, due to the community's habit of littering and lack of awareness about waste sorting. Despite efforts from the village government, including forming a Working Group (POKJA) and collaborating with UIN Raden Intan Lampung students, waste sorting remains a key issue. This research examines the effectiveness of waste management in the village, focusing on POKJA's challenges and potential solutions, such as the Sipitung program. The study uses observations, interviews, and participation in waste management activities to assess program success and identify obstacles. The lack of public awareness increases POKJA's workload and costs. The Sipitung innovation offers a potential solution by simplifying sorting and involving community participation. To improve waste management, increased education and awareness campaigns are necessary to encourage sustainable behavior.)